Ganame Adama - Ninigui (Yatenga Province), Burkina Faso - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Ganame Adama is a farmer with 10 children and two wives from the village Ninigui in Burkina Faso. He talks in the video about how using conservation farming techniques and optimizing the use of water through stone dams, he has adapted successfully to the changes in the rainfall patterns. As Ganame Adama himself puts it "with the climate change, we also have to change. We need ideas".